2003
DOI: 10.1523/jneurosci.23-06-02251.2003
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Neurons in the Middle Temporal Visual Area After Long-Standing Lesions of the Primary Visual Cortex in Adult New World Monkeys

Abstract: The retinotopic organization of the middle temporal visual area (MT) was determined in six adult owl monkeys and one adult marmoset 69 d to 10 months after lesions of the dorsolateral primary visual cortex (V1). The lesions removed were limited to extensive parts of the representation of the lower visual quadrant in V1. Microelectrodes were used to record from neurons at numerous sites in MT to determine whether parts of MT normally devoted to the lower visual quadrant (1) were unresponsive to visual stimuli, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 59 publications
6
43
0
Order By: Relevance
“…Our TP projection pattern correlates to findings by Lyon et al 2003. That research found that PD projects to TP, but PC does not.…”
Section: Secondary Visual Pathway Temporal Cortical Areassupporting
confidence: 88%
See 4 more Smart Citations
“…Our TP projection pattern correlates to findings by Lyon et al 2003. That research found that PD projects to TP, but PC does not.…”
Section: Secondary Visual Pathway Temporal Cortical Areassupporting
confidence: 88%
“…From those findings and ours, further research would need to be done to determine if the far ventral portion of PC does project to TA, or if the projections we are seeing are from PP, even though our micrographs of the injection site do not uncover tracer from that injection as far ventral as PP. Also in that research by Lyon et al (2003), they found that PP and not PC projected to TI. This projection in our study is most likely a PP to TI projection.…”
Section: Secondary Visual Pathway Temporal Cortical Areasmentioning
confidence: 88%
See 3 more Smart Citations